Human lower extremity joint moment prediction: A wavelet neural network approach - Ardestani, Marzieh Mostafavizadeh; Zhang, Xuan; Wang, Ling; Lian, Qin; Liu, Yaxiong; He, Jiankang; Li, Dichen; Jin, Zhongmin (Expert systems with applications, 2014)
•WNN is proposed as a real-time surrogate for joint moment prediction.•WNN predicts joint moments based on GRFs and EMG signals.•Generalization ability is tested for a new subject and a new gait pattern. Joint moment is one of the most important factors in human gait analysis. It can be calculated using multi body dynamics but might not be straight forward. This study had two main purposes; firstly, to develop a generic multi-dimensional wavelet neural network (WNN) as a real-time surrogate model to calculate lower extremity joint moments and compare with those determined by multi body dynamics approach, secondly, to compare the calculation accuracy of WNN with feed forward artificial neural network (FFANN) as a traditional intelligent predictive structure in biomechanics. To aim these purposes, data of four patients walked with three different conditions were obtained from the literature. A total of 10 inputs including eight electromyography (EMG) signals and two ground reaction force (GRF) components were determined as the most informative inputs for the WNN based on the mutual information technique. Prediction ability of the network was tested at two different levels of inter-subject generalization. The WNN predictions were validated against outputs from multi body dynamics method in terms of normalized root mean square error (NRMSE (%)) and cross correlation coefficient (ρ). Results showed that WNN can predict joint moments to a high level of accuracy (NRMSE<10%, ρ>0.94) compared to FFANN (NRMSE<16%, ρ>0.89). A generic WNN could also calculate joint moments much faster and easier than multi body dynamics approach based on GRFs and EMG signals which released the necessity of motion capture. It is therefore indicated that the WNN can be a surrogate model for real-time gait biomechanics evaluation.